Study of Acute and Chronic Antihyperglycemic Activity of Methanolic Extract of Salvia mirzayanii Rech. & Esfand. in Rats (Journal of Medicinal Plants, 2010)
Background: In folk medicine, there are many uses of useful effects of some medicinal plants for treatment of disease. In traditional medicine of Kerman province, Salvia mirzayanii Rech. & Esfand. (Lamiaceae) or Mor-e-Porzo applies for treatment of diabetes mellitus. Literature reviews showed another species of Salvia had antidiabetic effects. Objective: In this study anti hyperglycemic activities of this plant were evaluated. Methods: Eleven group (n=7) of male white rats (six normal and five diabetic) used. Diabetes induced by IP injection of streptozocin (STZ) (64 mg/kg). Diabetes was allowed to develop in these STZ treated rat over of 24h, and animals treated by 50, 100, 200, 400 mg/kg of the dried metanolic extract by IP injection for 24 hours and 400 mg/kg for 12 days. Finally, surgery carried out on these animals and liver and pancreas studied histopathologically. For statistic, used ANOVA with Turkeyschr('39') post hoc. Results: The maximal reduction in the blood glucose concentration of the fasted rats occurred at extract 400 mg/kg dose of extract. This dose (400 mg/kg) significantly reduced the blood glucose concentrations (p<0.01). On the other hand, histopathological studies showed this extract could repair and increase blood supply of pancreatic cells of these diabetic animals. Conclusion: Methanolic extract of S. mirzayanii could reduce blood glucose of these diabetic animals and its considerable effects on damaged pancreatic tissue, persuade the complemented studies and investigation on this plant.